The Effect of Direct Reading Thinking Activity (DRTA) On Students’ Reading Comprehension of The Seventh Grade Students - Epa Patmala; Tri Indah Rezeki (Journal of Elementary School Education, 2022)
This study aims to determine the effect of Direct Reading Thinking Activity (DRTA) on the students’ reading comprehension of the seventh-grade students. This research applied a quantitative research approach with a quasi-experimental design. The dependent variable is reading comprehension and the independent variable is the Direct Reading Thinking Activity strategy. The subject of this research was 50 students of the seventh-grade students at SMP Nusa Indah and consists of 25 students as the experimental class and 25 students as the control class. The experimental class was treated by using Direct Reading Thinking Activity (DRTA), while the control class was taught by conventional method. The instruments were used in this study were tests and observations. The tests were used to collect the data of the students’ reading comprehension of both of the classes. After the data was collected, the data analysis was carried out by comparing the results of the average value. The result of the analysis indicated that the mean of post-test score (85,28) of the experimental class was higher than the mean of post-test score (51,52) of the control class. It means that Ha was accepted. Therefore, it can be concluded that there was significant effect of Direct Reading Thinking Activity (DRTA) strategy after giving treatment.